2009
DOI: 10.4061/2009/807379
|View full text |Cite
|
Sign up to set email alerts
|

A Classification System to Detect Congestive Heart Failure Using Second-Order Difference Plot of RR Intervals

Abstract: A classification system to detect congestive heart failure (CHF) patients from normal (N) patients is described. The classification procedure uses the k-nearest neighbor algorithm and uses features from the second-order difference plot (SODP) obtained from Holter monitor cardiac RR intervals. The classification system which employs a statistical procedure to obtain the final result gave a success rate of 100% to distinguish CHF patients from normal patients. For this study the Holter monitor data of 36 normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Hence, it is usually chosen depending upon the character of the data [16]. In the present study an approach similar to the developed in previous works [22,23] was used to select the optimal ρ for each single Pwave feature. Thus, CTM was computed for radius of 0.1, 0.2, .…”
Section: Central Tendency Measurementioning
confidence: 98%
“…Hence, it is usually chosen depending upon the character of the data [16]. In the present study an approach similar to the developed in previous works [22,23] was used to select the optimal ρ for each single Pwave feature. Thus, CTM was computed for radius of 0.1, 0.2, .…”
Section: Central Tendency Measurementioning
confidence: 98%
“…The diagnoses reliability, however, might be increased if the screening test of heart failure could be assisted by signal processing techniques and biomedical analysis. In the past years, several works [1115] have shown the possibility of classifying subjects with heart failure. For instance, Işler and Kuntalp (2007) using short-term heart rate variability (HRV) intervals have shown that normalizing classical HRV and entropy measures can lead to high levels of sensitivity (82.76%) and specificity (100%).…”
Section: Introductionmentioning
confidence: 99%
“…2009;Engin 2007;Maurice E.Cohen 1996;Dabanloo et al 2010;Işler Y n.d.). Some of them considered Heart Rate Variability (HRV) of ECG signals (Işler & Kuntalp 2007;Kamath 2012b;Işler Y n.d.;Kannathal et al 2006;Thuraisingham 2010). In both cases, hidden important information (such as wavelet, eigenvector methods, Poincare, RR interval, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…have been used as classifier. Poincare plot and the SODP are commonly used methods as non-linear analysis of the components in biomedical signals (Işler Y n.d.;Thuraisingham 2010;Karmakar et al 2009;Maurice E.Cohen 1996;Dabanloo et al 2010). It is also known that poincare plot is an example of chaotic system (Maurice E. Cohen 1996).…”
Section: Introductionmentioning
confidence: 99%